Studi Pendahuluan Kemampuan Awal Berpikir Kritis Siswa Sekolah Dasar SDN Tunge 2 Wates Kediri - Utami, Ririn Puji; Muksar, Makbul; Rufiana, Intan Sari (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The research focus in this article is to describe the results of preliminary research and initial critical thinking skills in elementary school students, especially in mathematics subjects. The research subjects were class VI students at SDN Tunge 2, Wates District, Kediri Regency, Academic Year 2023/2024. The research method used in this article is descriptive qualitative. Data was obtained through critical thinking skills instruments, questionnaires, observation sheets, and interviews. The data was then analyzed descriptively. The results of questionnaires and interviews show that most teachers teach by lectures and assignments. The research results from the critical thinking ability instrument show that the initial ability to think critically overall it is still very lacking. Critical thinking ability is measured using six indicators which includes  interpretation, analysis, inference, evaluation, explanation and self-regulation. The highest indicator of critical thinking ability is interpretation with a gain percentage of 32.14%, while the lowest indicator is explanation with a gain percentage of 1.43%.